CORAK ISLAM TRADISIONAL DAN PERUBAHAN SOSIAL DALAM FIGUR PEMIMPIN KEAGAMAAN BAGI MASYARAKAT MULYOJATI METRO BARAT KOTA METRO - Nurjanah, Siti (JURNAL TAPIS, 2012)
AbstractMulyojati society is unique in carrying out religious activities. They are more inclined to religious leaders around since the beginning and unlikely to figure other leaders that also tried to make changes. This fact has an impact on the difficulty of public mindset change has occurred even though the dynamics have changed. This paper is the result of research on the influence of religious leaders on religious figures in urban Mulyojati communities that district west metro city metro in 2010. The research objective was to explore the opinions and looking for a traditional Islamic style that characterizes the religious life of local communities. This research is a qualitative study using descriptive analysis. Samples determined by purposive sampling. Data obtained by direct observation by observation, structured interviews and documentation methods. Analysis of the data is using the method of qualitative analysis. The results showed that the traditional Islamic patterns and social changes that characterize the life of religious communities is very thick, which is characterized by a slow process of social change, because it is still difficult to accept the views of others. Whereas these people realistically region 16 b and 16 c have progressed rapidly in the field of religion, economics and education. Figure of the religious leaders of the religious in the above areas have a very strong effect to create a comprehensive understanding of Islam. In the other hand, leader who was not ready to accept change as it is still put forward opinions of scholars of the past and made no attempt to elaborate an understanding of the present and the lack of respect for the opinion of others. Keywords: Traditional Islam, social change, religious leaders.